Extreme events in the La Plata basin: a retrospective analysis of what we have learned during CLARIS-LPB project - Carril, Andrea Fabiana (2016)
Extreme climate events over the La Plata basin (LPB) can produce significant impacts due to the importance of the regional agriculture and hydroelectric power production for the local economy. Progress on describing, projecting and understanding extremes in LPB, in the framework of the CLARIS-LPB Europe-South America Network for Climate Change Assessment and Impact Studies in La Plata Basin Project, are reviewed. The paper is based on recent studies and publications, as well as some new diagnostics as indicators of works in progress, and can be considered as an update for the LPB region of previous reviews by Cavalcanti et al. (2015; J Hydrol 523:211-230) and Rusticucci (2012; Atmos Res 106:1-17). Despite the significant advances on regional extremes, some gaps have been identified, and many challenges remain. Much of the recent progress considers temperature and precipitation extremes on timescales varying from synoptic to long-term variability and climate change, essential for impact and vulnerability assessments. Research lines on extremes requiring further efforts include the relative roles of local versus remote forcings, the impact of land use and land management changes, the specific role of soil moisture and land-atmosphere feedbacks as catalysts for heat waves, the impact of the local inhomogeneities in soil moisture, feedback and uncertainties in projections of extremes, as well as seasonal forecast and climate change attribution studies. We suggest combining intensive monitoring and modelling to address these issues.